Cancer preventive services, socioeconomic status, and the Affordable Care Act. Issue 9 (9th January 2017) - Cooper, Gregory S.; Kou, Tzuyung Doug; Dor, Avi; Koroukian, Siran M.; Schluchter, Mark D.
Abstract : BACKGROUND: Out‐of‐pocket expenditures are thought to be an important barrier to the receipt of cancer preventive services, especially for those of a lower socioeconomic status (SES). The Affordable Care Act (ACA) eliminated out‐of‐pocket expenditures for recommended services, including mammography and colonoscopy. The objective of this study was to determine changes in the uptake of mammography and colonoscopy among fee‐for‐service Medicare beneficiaries before and after ACA implementation. METHODS: Using Medicare claims data, this study identified women who were 70 years old or older and had not undergone mammography in the previous 2 years and men and women who were 70 years old or older, were at increased risk for colorectal cancer, and had not undergone colonoscopy in the past 5 years. The receipt of procedures in the 2‐year period before the ACA's implementation (2009‐2010) and after its implementation (2011 to September 2012) was also identified. Multivariate generalized estimating equation models were used to determine the independent association and county‐level quartile of median income and education with the receipt of testing. RESULTS: For mammography, a lower SES quartile was associated with less uptake, but the post‐ACA disparities were smaller than those in the pre‐ACA period. In addition, mammography rates increased from the pre‐ACA period to the post‐ACA period in all SES quartiles. For colonoscopy, in both the pre‐ and post‐ACA periods, there was an association between uptake and educational level and, to some extent, income. However, there were no appreciable changes in colonoscopy and SES after implementation of the ACA. CONCLUSIONS: The removal of out‐of‐pocket expenditures may overcome a barrier to the receipt of recommended preventive services, but for colonoscopy, other procedural factors may remain as deterrents. Cancer 2017;123:1585–1589. © 2017 American Cancer Society . Abstract : Although it has been assumed that the elimination of out‐of‐pocket expenses will reduce socioeconomic disparities in cancer screening, there is little empirical evidence to support this contention. Using Medicare data, this study shows that with the Affordable Care Act, disparities have decreased for screening mammography but not colonoscopy.